Nutrient Assessment of Some Tropical Leaf Meals - Fawolu, Taiwo Sunday; Igbasan, Frances Adegbaye (International Journal of Environment, Agriculture and Biotechnology, 2019)
Nutrient availability of five tropical leaves were carried out, the tropical leaves were harvested fresh and the leaves were dried under room temperature (air-dry) until a moisture content of less than 11.00% was obtained in all the leaves. The air-dried leaves were milled and analyzed for their; proximate composition, mineral composition, anti-nutritional composition, fibre fractions, amino-acid concentration and biophysical properties. The results revealed that the crude protein content ranged between 30.77% in amaranthus and 44.09% in fluted pumpkin, fat content ranged between 6.11% in fluted pumpkin and 9.13% in moringa, ash content ranged between 9.28% in cotton seed leaf and 19.29% in amaranthus, crude fibre ranged between 8.10% in squash-gourd and 15.32% in fluted pumpkin and CHO ranged between 14.85% in squarch-gourd and 30.57% in cotto seed leaf. The macro and micro minerals analysis and essential and non-essential amino acid analysis revealed that all the parameters analysed for were reasonably high, the anti-nutritional factors of the leaves were very low, the fibre fractions were within range and the biophysical characteristic were normal.This study shows that the leaves were rich in nutrients that are good for poultry production.